The Surprise Friend - West, Cindy; Mateu, Francese (Racine, Wis. : Western Pub. Co., 1990)
Daisy Duck surprises Minnie Mouse with a birthday party after tricking her into choosing a gift for a "good friend."
"A Golden book, New York."
"Level one, grades K-1"--Cover p. [1].
Keywords: Daisy Duck (Fictitious character) -- Fiction; Minnie Mouse (Fictitious character) -- Fiction; Surprise birthday parties -- Fiction